Budaya Makan Bersama dalam Perayaan Pengucapan Syukur Sebagai Tindakan Simbolik Integrasi Sosial di Minahasa Tenggara. - Rivenhard Runturambi (Mahesa Research Center, 2022)
This study aims to describe the understanding and meaning of the celebration of thanksgiving as a symbolic act of social integration in Southeast Minahasa. For the people of Southeast Minahasa who are increasingly modern, the celebration of thanksgiving marked by eating and drinking together is a hereditary legacy as an expression and overflow of gratitude itself. The research used is qualitative research, people believe that eating together in a celebration is to build memory to maintain a relationship on an ongoing basis as Elizabeth Peres' perspective on